To the Question of the Reasons for Decrease in the Durability of Cutting Tools with a Diamond-Like Coating - Lieberman Yacov (EDP Sciences, 2021)
In this study, we investigate the reasons for the decrease in the durability of cutting tools with diamond-like carbon coating. We formulated a previously unexplored assumption that the destruction of the coating may occur due to the dissimilarity of the thermal expansion coefficients of the latter and the substrate material. To verify this assumption, we developed a special technique based on the theory of elasticity and carried out a study of several end mills and turning tools made of different materials. The results of our research confirm the validity of the hypothesis. We further propose methods of combating the discovered reason for the decrease in tool life.